Pelatihan Penggunaan Matlab bagi MGMP IPA Wilayah III Polman - Susanto, Agus; Palloan, Pariabti; Arsyad, Arie Arma (Sipakaraya : Jurnal Pengabdian Masyarakat, 2024)
This program was in the form of training on the use of matlab for MGMP IPA Region III Polman. The benefits obtained from this PkM activity were 1) teachers had knowledge about the concept of matlab, 2) teachers had skills in using matlab . This PkM partner is made up of 32 teachers from MGMP IPA Region III Polman. The results of the activities that have been carried out show that the dominant teacher was able to operate and utilize matlab as a learning medium.